Pengaruh Self Efficacy Dan Dukungan Orang Tua Terhadap Kemandirian Belajar Mahasiswa Pendidikan Ekonomi Universitas Negeri Padang - Ghina Mufidah; Elvi Rahmi (Universitas Negeri Padang, 2024)
The purpose of this study is to examine the effects of parental support and self-efficacy on the learning independence of Universitas Negeri Padang students studying economics. This is a descriptive associative research design that makes use of primary data sources. Questionnaires are distributed as part of the data collection process. Purposive sampling is the method of sampling, and SPSS version 25's multiple regression analysis tool—which comprises the Classical Assumption Test, Multiple Regression Test, and Hypothesis Testing—is used for the analysis. The following are the research findings related to the stated issues: (1) Self-efficacy has a major impact on the learning independence of Universitas Negeri Padang students studying economics, and (2) there is a significant influence of parental support on learning independence. learning from economic education students at Universitas Negeri Padang.